THE INFLUENCE OF AUDIT QUALITY, OPERATIONAL AUDIT, TECHNOLOGY AUDIT, AND AUDIT REPORTS ON THE FINANCIAL STATEMENTS OF MSMEs IN MEDAN CITY - Wijaya, Jerry; Sipahutar, Tetty Tiurma Uli; , Munawarah (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2025)
Finding out how audit quality, operational audits, technology audits, and audit reports affect financial reporting for MSME was the main goal of this research. The sampling procedure employs a technique known as purposive sampling. In order to gather data, a questionnaire was used. Applying a number of linear models is one strategy for data analysis. Numerous statistical evaluations are used, including the time-honored assumption test, validity, reliability, multicollinearity, and normalcy tests. The following are the results of the study: X1) The impact of MSME financial statements on audit quality is positive (r=0.175); X2) There is a positive correlation between MSME financial reports and operational audits (r=0.336); X3) There is a negative correlation between MSME financial reports and technology audit (r= -0.206); and X4) There is a positive correlation between MSME financial reports with audit reports (r=0.212). Audit reports, along with operational audits and technology audits, impact MSME financial reporting. Audit quality does not impact MSME financial reporting.